際際滷

際際滷Share a Scribd company logo
Translating Quadratic
Function from Standard Form
into Vertex Form if  = 
Mathematics 9
Standard From and Vertex Form of
Quadratic Function
Standard Form
 = 2
+  + 
Vertex Form
 =     2
+
To translate quadratic function
from standard form to vertex
form, you need to know the
following:
1. Completing the Square Method
2. Factoring
Standard to Vertex Form
 Steps for translating quadratic function from standard to
vertex form if  = 
Step 1: Since the equation is in the standard form  = 2 +
 + , and we want to convert it into the form of  =
    2 + , then the first thing that we need to do is
transpose  to the other side of equal sign.
Example 1:
 = 2 + 4 + 7
  7 = 2
+ 4
Standard to Vertex Form
 Steps for translating quadratic function from standard to
vertex form  = 
Step 2: Perform completing the square. The goal of this method is to make a
perfect square trinomial and it will only happen if the coefficient of 2
or the
value of a is equal to 1. Since the coefficient of 2
in the example below is
equal to 1, then we can immediately perform completing the square. For this
situation, we will going to add



to the both sides of equation.
  7 +



= 2 + 4 +



   +  =  
+  + 
Since  = 4, then



= 4
Standard to Vertex Form
 Steps for translating quadratic function from standard to
vertex form  = 
Step 3: Simplify both sides of equation.
   +  =  
+  + 
To simplify, add -7
and 4
Since this is already a
perfect square trinomial,
then rewrite it as square of
binomial:
 +

2
2
   =  +
Standard to Vertex Form
 Steps for translating quadratic function from standard to
vertex form  = 
Step 4: Transpose the constant term to the other side of the
equal sign so that ONLY   will be left.
   =  +   Since the constant is -3,
when you transpose it, the
sign will change.
 =  +  
+ 
This is already the vertex
form of the equation
 =   +  + 
Final Answer
More Examples
Translating Standard Form into Vertex Form when  = 1
Example 1
 =  
+  +  Quadratic in Standard Form
   =  
+  Transpose 10 to the left
   + _____ =   +  + _____
Completing the square:
Since  = 6, the

2
2
=
6
2
2
= 9
   +  =   +  +  Add 9 to both sides of equation
   =  +   Transpose -1 so that only y will be
left.
 =  +  
+  Final Answer
Find the vertex form of the function  = 2
+ 6 + 10.
Example 2
 =  
+    Quadratic in Standard Form
 +  =  
+  Transpose -3 to the left
 +  + _____ =   +  + _____
Completing the square:
Since  = 2, the

2
2
=
2
2
2
= 1
 +  +  =   +  +  Add 1 to both sides of equation
 +  =  +   Transpose 4 so that only y will be
left.
 =  +  
  Final Answer
Find the vertex form of the function  = 2
+ 2  3.

More Related Content

Translating standard form into vertex form if a=1

  • 1. Translating Quadratic Function from Standard Form into Vertex Form if = Mathematics 9
  • 2. Standard From and Vertex Form of Quadratic Function Standard Form = 2 + + Vertex Form = 2 +
  • 3. To translate quadratic function from standard form to vertex form, you need to know the following: 1. Completing the Square Method 2. Factoring
  • 4. Standard to Vertex Form Steps for translating quadratic function from standard to vertex form if = Step 1: Since the equation is in the standard form = 2 + + , and we want to convert it into the form of = 2 + , then the first thing that we need to do is transpose to the other side of equal sign. Example 1: = 2 + 4 + 7 7 = 2 + 4
  • 5. Standard to Vertex Form Steps for translating quadratic function from standard to vertex form = Step 2: Perform completing the square. The goal of this method is to make a perfect square trinomial and it will only happen if the coefficient of 2 or the value of a is equal to 1. Since the coefficient of 2 in the example below is equal to 1, then we can immediately perform completing the square. For this situation, we will going to add to the both sides of equation. 7 + = 2 + 4 + + = + + Since = 4, then = 4
  • 6. Standard to Vertex Form Steps for translating quadratic function from standard to vertex form = Step 3: Simplify both sides of equation. + = + + To simplify, add -7 and 4 Since this is already a perfect square trinomial, then rewrite it as square of binomial: + 2 2 = +
  • 7. Standard to Vertex Form Steps for translating quadratic function from standard to vertex form = Step 4: Transpose the constant term to the other side of the equal sign so that ONLY will be left. = + Since the constant is -3, when you transpose it, the sign will change. = + + This is already the vertex form of the equation = + + Final Answer
  • 8. More Examples Translating Standard Form into Vertex Form when = 1
  • 9. Example 1 = + + Quadratic in Standard Form = + Transpose 10 to the left + _____ = + + _____ Completing the square: Since = 6, the 2 2 = 6 2 2 = 9 + = + + Add 9 to both sides of equation = + Transpose -1 so that only y will be left. = + + Final Answer Find the vertex form of the function = 2 + 6 + 10.
  • 10. Example 2 = + Quadratic in Standard Form + = + Transpose -3 to the left + + _____ = + + _____ Completing the square: Since = 2, the 2 2 = 2 2 2 = 1 + + = + + Add 1 to both sides of equation + = + Transpose 4 so that only y will be left. = + Final Answer Find the vertex form of the function = 2 + 2 3.